Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.conbuildmat.2013.03.094
|View full text |Cite
|
Sign up to set email alerts
|

Moment redistribution in continuous FRP reinforced concrete beams

Abstract: The main purpose of this paper is to assess moment redistribution in continuous concrete beams reinforced with fibre reinforced polymer (FRP) bars. A numerical technique based on equilibrium of forces and full compatibility of strains has been developed to evaluate the moment-curvature relationships and moment capacities of FRP and steel reinforced concrete sections. Moment redistribution has then been assessed by comparing elastic and experimental moments at failure, and moment capacity at critical sections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 16 publications
3
21
0
Order By: Relevance
“…Santos et al [15] conducted an experimental and numerical study of ductility and moment redistribution in continuous GFRP reinforced concrete T-shaped beams. Kara and Ashour [16] assessed redistribution of moments in FRP reinforced concrete beams by comparing the actual moments at ultimate with the corresponding elastic values. More recently, Mahroug et al [17,18] reported test results of a series of BFRP and CFRP reinforced concrete continuous slabs.…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al [15] conducted an experimental and numerical study of ductility and moment redistribution in continuous GFRP reinforced concrete T-shaped beams. Kara and Ashour [16] assessed redistribution of moments in FRP reinforced concrete beams by comparing the actual moments at ultimate with the corresponding elastic values. More recently, Mahroug et al [17,18] reported test results of a series of BFRP and CFRP reinforced concrete continuous slabs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been extensive research to investigate the flexural behavior of FRP reinforced concrete members [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Many design approaches to calculate the deflection of FRP reinforced concrete members have been proposed in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…This property raised concerns about the ability of FRP-RC members to redistribute moments between the critical sections. However, moment redistribution in such elements was reported in many studies (Mostofinejad 1997;Habeeb and Ashour 2008;ElMogy et al 2010ElMogy et al , 2011Matos et al 2011;Kara and Ashour 2013;Santos et al 2013;El-Salakawy 2014, 2016). In these studies, parameters such as material type, reinforcement ratio and configuration, concrete strength, stirrup spacing in the context of beams with rectangular and T-section were investigated; however, the beams were tested under symmetrical loading conditions.…”
Section: Problem Definitionmentioning
confidence: 99%